I am still here: Lessons learned from incorporating social presence in remote teaching - Kluyts, Marike; Nell, Annalene; Coetzer, Zonnike; Du Plooy, Charlene; Norval, Gawain (My University, 2022)
This chapter shares the reflections of a group of teachers who taught on an enrichment programme for secondary school learners run by a research-intensive higher education institution in South Africa. The aim of the programme is to increase eligibility and access to higher education, through providing meaningful educational inputs to help prepare learners for the university environment (SETMU 2020: 5). The continuation of lockdown learning in 2021 a􀀵ected the mode of delivery of the enrichment programme, resulting in the programme being presented remotely, using both synchronous and asynchronous inputs. Remote teaching and learning have stripped away many aspects, such as ease of connection, central to ‘brick-and-mortar’ teaching that helped both learners and teachers successfully complete their respective activities pre-Covid-19. This has resulted in a sense of disconnection between teachers and learners, as well as among learners. To remedy these feelings of disconnection, the teachers incorporated elements of the Community of Inquiry Framework (Garrison, Anderson and Archer 1999) in their remote teaching practices. This framework highlights the importance of three presences in developing successful online classes, namely social, cognitive, and teaching presences. This reflection focusses on how creating a stronger social presence can enable the development of dynamic and strong remote learning environments (Darby and Lang 2019: 112), which provide students with the opportunity to construct and confirm meaning. Based on a qualitative textual analysis of personal reflections written by the teachers, three important aspects were identified to facilitate learner interaction: (1) Familiarity (creating spaces where learners feel seen and heard); (2) Being present (‘showing up’ in the asynchronous space as well as the synchronous); and (3) Online identity (teachers incorporating their unique personalities into the online sessions). Thus, going forward it illustrates the importance of explicitly creating a social presence in remote classes to improve learning.